PENGARUH CORPORATE SOCIAL RESPONSIBILITY, UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE, dan CAPITAL INTENSITY TERHADAP AGRESIVITAS PAJAK (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2013-2015) - Efayuani, 13.05.52.0100; Setyowati, Widhy (Students' Journal of Accounting and Banking, 2017)
This study aims to examine and analyze the influence of Corporate Social Responsibility, firm size, proftability, leverage and capital intensity to the tax aggressiveness of empirical study of manufacturing companies listed on the Indonesia Stock Exchange. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2013-2015. The population in this study amounted to 462 manufacturing companies listed on the Indonesia Stock Exchange. The sampling technique was chosen using purposive sampling method and obtained 271 manufacturing companies based on certain criteria. The results showed that Corporate Social Responsibility had positive and no significant effect on tax aggressiveness, firm size had negative and significant effect on tax aggressiveness, profitability and leverage had positive and no significant effect on tax aggressiveness, and capital intensity had a positive and significant effect on tax aggressiveness.Keywords: Tax Aggressiveness, Corporate Social Responsibility, Company Size, Profitability, Leverage and Capital Intensity